The Prospects for Reproductive Health Rights Protection in Nigeria - Aloamaka, Patrick Chukwunonso; Ibekwe, Favour Adaeze; Udo, Edidiong Jacob (PREDESTINASI, 2019)
There exist prospects and opportunities for the protection of Reproductive Health Rights in the Nigerian Legal System. Nigeria has ratified severalInternational/Regional Human Rights instruments which seek to protect reproductive rights, there are some Human Rights provisions contained in the constitution, some other provisions on Federal and State Legislations that are gender based. There are also the reports on Millennium Development Goals and National Reproductive Health Policies which shows that there are prospects and opportunities that the government can protect women’s reproductive health and rights in Nigeria. Nonetheless, there is undoubtedly room for improvement in the protection of this peculiar genre of rights of women in Nigeria and this work proffers country-centric recommendations which cut across options of amending relevant Constitutional and Federal/State legislations on Reproductive Health Rights. The country will certainly benefit from an implementation of the National Reproductive Health policies that have evolved overtime and domesticating some of the international and regional instruments that has been ratified like CEDAW whilst enacting a National Reproductive Health Law by National Assembly which will be uniformly adopted and implemented  throughout the country.